KAJIAN LEKSIKOSTATISTIK BAHASA MUNA, BAHASA CIA-CIA DAN BAHASA WOLIO DI SULAWESI TENGGARA - La Ode Rely (Kantor Bahasa Provinsi Gorontalo, 2017)
The Muna language, Cia-Cia language and Wolio language are cognatelanguages in Southeast Sulawesi and they have kinship with each other.This research aimed to know the level of kinship between Muna language, Cia-Cia language and Wolio language in Southeast Sulawesi, when Muna language separate from, Cia-Cia language and Wolio language, and what is the estimated age among the Muna language, Cia - Cia language and Wolio.Descriptive method and lexicostatistics technique are used in this research. The result showed that the percentage of kinship of Muna language and Cia-Cia language was 48%. Separate time between Muna language and Cia-Cia language is estimated from 183 to 463 Masehi. The percentage of kinship of Muna language and Wolio language was 45%. Separate time between the Muna language and Wolio language is estimated 23 Masehi until 323 Masehi. The percentage of kinship of Cia-Cia language and Wolio languages was 44%. Separate time between Cia-Cia language and Wolio language is estimated 28 Before Masehi to 274 Masehi. The age of Muna language around 183 to 463 Masehi was separated from it's mother tongue with Cia-Cia Language and around 23 Masehi to 323 Masehi was separated from it's mother tongue with Wolio language. They were cognate language, one family or one language family.